Sediminibacterium roseum sp. nov., isolated from sewage sediment - Song, Yali; Jia, Jianqiang; Liu, Dongmei; Choi, Lina; Wang, Gejiao; Li, Mingshun (International journal of systematic and evolutionary microbiology, 2017)
A novel bacterial strain, designated SYL130 , was isolated from the sewage sediment of a park in Busan, Korea. The strain was aerobic, producing orange colonies on R2A agar. Cells were single, Gram-stain-negative rods and were motile by gliding. Phylogenetic analyses, based on 16S rRNA gene sequences, showed that strain SYL130 was most closely related to Sediminibacterium aquarii JCM 31013 (96.1 %). The major fatty acids (>5 % of the total) of strain SYL130 were iso-C15 : 0 (28.3 %), iso-C15 : 1 G (23.2 %), iso-C17 : 0 3-OH (9.6 %), anteiso-C15 : 0 (5.9 %) and iso-C16 : 0 3-OH (5.6 %). The major polar lipids were phosphatidylethanolamine, one unidentified phospholipid, one unidentified aminolipid, two unidentified aminophospholipids and six unidentified polar lipids. The predominant respiratory quinone was MK-7. The DNA G+C content was 47.8 mol%. Strain SYL130 had clearly differential characteristics to related species including the temperature and pH ranges for growth, and being positive for l-arabinose and maltose, and negative for α-galactosidase activity. On the basis of phenotypic, chemotaxonomic and genotypic analyses, strain SYL130 represents a novel species of the genus Sediminibacterium, for which the name Sediminibacterium roseum sp. nov., is proposed. The type strain Sediminibacterium roseum is SYL130 (=KCTC 52860 =CCTCC AB 2017082 ).